An overview on non-ideal vibrations - Balthazar, José Manoel [UNESP]; Mook, D. T.; Weber, H. I.; Brasil, RMLRF; Fenili, A.; Belato, D.; Felix, JLP (Kluwer Academic Publ, 2003)
We analyze the dynamical coupling between energy sources and structural response that must not be ignored in real engineering problems, since real motors have limited output power.
Keywords: limited power supply; non-ideal vibrations; Sommerfeld effect